1999
DOI: 10.2135/cropsci1999.0011183x003900030039x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Rotylenchulus reniformis and Meloidogyne incognita Race 3 in the Major Cotton Cultivars Planted Since 1950

Abstract: The southern root‐knot nematode, Meloidogyne incognita race 3 (Kofoid & White) Chitwood, and the reniform nematode, Rotylenchulus reniformis Linford & Oliveira, are the most widespread and economically important nematode pests of Upland cotton (Gossypium hirsutum L.) and Pima cotton (G. barbadense L.) in the USA. Progress in the development of nematode‐resistant cotton cultivars is unclear. Plant breeders often have selected for nematode tolerance by measuring cotton yield in nematode‐infested fields but seldo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Robinson et al (1999) reported that Pima S-5, Pima S-6 and Pima S-7 were susceptible to root-knot nematode and that Pima S-2 was moderately resistant to root-knot nematode. However, in our tests, Pima S-2 was susceptible to root-knot nematode and had only slightly less infection than susceptible Pima S-7.…”
Section: Presence Of the Caps And Ssr Markers In 23 Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson et al (1999) reported that Pima S-5, Pima S-6 and Pima S-7 were susceptible to root-knot nematode and that Pima S-2 was moderately resistant to root-knot nematode. However, in our tests, Pima S-2 was susceptible to root-knot nematode and had only slightly less infection than susceptible Pima S-7.…”
Section: Presence Of the Caps And Ssr Markers In 23 Genotypesmentioning
confidence: 99%
“…However, its root-knot nematode resistance status has not been reported. Most Coker lines except Coker 100W were reported to be susceptible to root-knot nematodes (Robinson et al 1999). Based on these breeding histories, the four genotypes with unknown phenotype are likely to be susceptible to root-knot nematodes.…”
Section: Presence Of the Caps And Ssr Markers In 23 Genotypesmentioning
confidence: 99%
“…Pima cottons (G. barbadense L.) are good hosts for M. incognita (Robinson et al 1999), and in preliminary studies with interspeciWc Pima S-7 £ Acala NemX progenies, we observed some genotypes with levels of nematode resistance higher than the resistant parent indicating strong transgressive segregation and epistasis eVects on resistance. To further characterize the transgressive segregation for resistance in interspeciWc crosses of susceptible G. barbadense cv.…”
Section: Introductionmentioning
confidence: 75%
“…A susceptible control S. lycopersicum "Rutgers" (LA 1090) was included. This genotype has been shown to support prolific reproduction of reniform nematodes [21]. In all, six randomized replications of 40 genotypes were tested against R. reniformis.…”
Section: Relative Response Of Four Tomato Species To Rotylenchulus Rementioning
confidence: 99%